Meat proteins in a high-fat diet have a substantial impact on intestinal barriers through mucus layer and tight junction protein suppression in C57BL/6J mice. Issue 10 (7th October 2019) - Hussain, Muzahir; Umair Ijaz, Muhammad; Ahmad, Muhammad Ijaz; Khan, Iftikhar Ali; Brohi, Sarfaraz Ahmed; Shah, Abid Ullah; Shinwari, Kamran Iqbal; Zhao, Di; Xu, Xinglian; Zhou, Guanghong; Li, Chunbao
Abstract : Protein diets are well known for body maintenance and weight loss. Abstract : Protein diets are well known for body maintenance and weight loss. However, it remains unclear whether and how different protein sources affect the intestinal epithelial integrity through tight junctions, mucus secretions and host immunity in diet-induced obesity. To evaluate possible effects, soybean, chicken and pork proteins either with low fat (12% kcal) or high fat (60% kcal) were administered to C57BL/6J mice for 12 weeks. Muc2 expression, tight junction proteins, goblet cells, and inflammatory cytokines in the colon and serum were measured. The intake of a high-fat pork protein diet decreased the number of goblet cells and inhibited Muc2 expression in the colon, which impaired the mucus barrier. Immunohistochemistry indicated decreased crypt depth and downregulation of tight junction proteins in high-fat diet fed mice, signifying losses of epithelial barriers. In addition, a pork protein diet reduces the key zonula occludens-1 and E-cadherin proteins. A high-fat meat protein diet induces colonic inflammatory injury by upregulating several key cytokines and increasing IL-1β, TNF-α, IL-6 and IFN-γ concentrations in serum. The intake of high-fat meat protein diets resulted in the impairment of the colon barrier through mucus suppression, downregulation of tight junctions, and gut inflammation in mice.